Visual and Demographic Risk Factors for Falls and the Impact of Cataract Surgery in Elderly Patients - Heidarzadeh, Hamid Reza; Derakhshan, Akbar; Shahri, Seyed Hossein Ghavami; Astaneh, Mohammad Reza Ansari; Bakhtiari, Elham; Rad, Saeed Shokouhi; Abrishami, Mojtaba (Journal of Ophthalmic and Vision Research, 2024)
Purpose: To evaluate the effect of cataract surgery and visual impairment and the associated risk factors on the frequency of falls among older adults in northeast Iran. Methods: This cross-sectional study, conducted between 2019 and 2020, analyzed the potential risk factors of falling in older adults over 50 years of age. To this end, 380 patients were randomly selected by convenience sampling and classified into two groups: those who had undergone cataract surgery in the last 12 months (surgery group) and those who had not (cataract group). The data were collected from the medical records and face-to-face interviews, and logistic regression was used to identify potential risk factors for falling. Results: The frequency of falls in the cataract and surgery groups was 18.9% and 11.6%, respectively. The mean decimal visual acuity of the dominant eye was significantly lower in the cataract group than in the surgery group (P < 0.001). There were no significant differences in the mean number of medications used, Charlson Comorbidity Index score, Instrumental Activities of Daily Living score, and 10-Meter Walk Test speed between the two groups. According to the results of backward logistic regression, taking more than four medications per day and slow gait speed were the most important factors influencing the frequency of falls in older adults. Conclusion: Logistic regression analysis indicated that undergoing cataract surgery is not a significant protective factor against falls. However, older adults in the surgery group experienced fewer falls than in the other group. Besides, the results suggest that taking more than four medications daily and having a slow gait speed are significant fall risk factors.